Diferensiasi Stadium Takizoit-Bradizoit pada Toxoplasma gondii - Suri Dwi Lesmana (Fakultas Kedokteran Universitas Riau, 2010)
Toxoplasma gondii is an intracellular parasite whose definite host is cat or felidae and intermediate host is human orother mammals. It causes congenital and acquisita toxoplasmosis. Infection with this apicomplexan parasite results inits dissemination throughout its host via the tachyzoite life stage. After dissemination, these tachyzoites differentiateinto bradyzoites within cyst and remain latent. These bradyzoites can transform back into tachyzoites and inimmunosupressed individuals this often results in symptomatic disease. Both tachyzoites and bradyzoites develop intissue culture and this crucial differentiation event can be studied. Interferon gamma (IFN ) is the main mediator intachyzoite-bradyzoite differentiation.